Open tibial fractures. Issue 2 (April 2017) - Fernandez, Miguel A.; Nanchahal, Jagdeep; Costa, Matthew L.
Abstract: Open fractures of the tibia are potentially life-changing injuries with huge costs to both patients and healthcare systems. These injuries require early coordinated interventions by senior orthopaedic and plastic surgical teams (orthoplastic) to reduce the risk of long-term complications and improve outcomes. Here we review clinical guidelines and developments in the evidence base to highlight key aspects of the coordinated care of open fractures of the tibia.